Comparative evaluation of ethanol versus citric acid in removal of oil-based calcium hydroxide from the apical third of root canal system - Naved, Nighat; Umer, Fahad (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the effectiveness of ethanol compared to citric acid in the removal of oil-based calcium hydroxide from the apical third of the root canal system using passive ultrasonic irrigation. Method: The in vitro study was conducted from September to October 2021 at the dental clinics of the Aga Khan University Hospital, Karachi, and comprised single-rooted teeth that were selected from institutional bank of extracted teeth. They were randomly divided into group A having 70% ethanol + passive ultrasonic irrigation, group B 10% citric acid + passive ultrasonic irrigation, group C positive controls and group D negative controls. The specimens were sectioned at 1mm and 3mm from the apex and examined under a dental operating microscope. A single examiner scored the specimens on two different occasions. Data was analysed using SPSS 25. Results: Of the 90 teeth, there were 40(44.4%) in each of the 2 experimental groups and 5(5.5%) in each of the 2 control groups. At 3mm apical sections, ethanol was significantly more effective in the removal of oil-based calcium hydroxide (p=0.01). However, at 1mm from the apex, there was no significant difference between the experimental groups (p=0.064). Intragroup comparison showed that for groups A and B, residual medicament at 1mm sections was significantly greater than at 3mm sections (p<0.001, p=0.003). Conclusion: Neither irrigant showed complete removal at 1mm and 3mm from the apex. However, at 3mm apical sections, 70% ethanol was significantly more effective compared to 10% citric acid. Key Words: Calcium hydroxide, Root canal medicament, Endodontics, Citric acid, Ethanol.